ABO(H) and Lewis blood group substances and disease treatment. Issue 3 (26th September 2021) - Liu, Junting; Wang, Deqing
Abstract: Since the early 20th century, scientists have determined that blood group antigens can be inherited. With more and more studies have been devoted to finding the relationship between blood groups and diseases, the relationship of ABO(H) and Lewis blood groups and the development of human diseases have been summarised. In addition, many studies have shown that blood group substances, such as blood group antigen or related antibody, play an important role in disease prevention and treatment. This review focuses on the advances of ABO(H), Lewis blood group substances in the treatment of diseases, which has important significance for the development of novel therapeutic methods.